Pengaruh Kompetensi SDM, Financial Literacy, Dan Pemanfaatan Teknologi Terhadap Kinerja UMKM Di Kota Jambi Tahun 2024 - Robby Erviando Z; Zulkipli; Riman Abimanyu; Muhammad Iqbal (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This research seeks to explore the determinants that impact the performance of Micro, Small, and Medium Enterprises (MSMEs). A quantitative method with a descriptive design was employed in this study. Data were collected through questionnaires distributed to 66 MSME participants. The analytical method applied was multiple linear regression using SPSS software. The findings reveal that human resource competence and financial literacy significantly and positively influence MSME performance in Jambi City. In contrast, technological adoption does not exhibit a significant or positive effect on their performance.